Doppler ocular ultrasound in patients with type 2 diabetes mellitus (Ukrainian Journal of Ophthalmology, 2023)
Purpose: To determine ocular blood flow parameters by Doppler ultrasound scanning in type 2 diabetic patients with different stages of diabetic retinopathy.Material and Methods: In this prospective study, forty-five patients (90 eyes) with type 2 diabetes mellitus were divided into three groups of 15 patients each: no diabetic retinopathy group (DR0), non-proliferative retinopathy (NPDR), and proliferative retinopathy (PDR) groups. Doppler indices such as systolic blood flow velocity (Vs), diastolic blood flow velocity (Vd), time-averaged maximum velocity (TAMXV), pulsatility index (PI) and resistivity index (RI) in the ophthalmic artery (OA), central retinal artery (CRA) and short posterior ciliary arteries (SPCA) were determined. ANOVA was used for quantitative comparisons between the three groups.Results: There was a significant (р
Keywords: type 2 diabetes mellitus; diabetic retinopathy; Doppler ultrasound; central retinal artery; ophthalmic artery; short posterior ciliary arteries